Structural Characteristics of The Semanggol Formation Along The East-West Highway Route 67 Baling Area, Kedah, Malaysia - Yuniarti Ulfa; Mohd Hafiz Hafizzy; Muhammad Farhan (Pusat Teknologi Bahan Galian Nuklir - BATAN, 2012)
The amounts of structural data available from the East-West Highway Route 67 of Baling Area have been used to unravel the structural characteristics of the Semanggol Formation, which comprises black mudstone, sandstone, tuffaceous sandstone, tuff, paraconglomerate, siliceous shale and chert. The area was cut by two sets of faults trending NW-SE and NE-SW. The main fault in this area is known as Bok Bak fault that is trending NW-SE and have moderately to steeply dips (40o-88o) as compared to the conjugate faults. Two sets of folds trending NE-SW and NW-SE were also identified in this area, where most of them are symmetrical fold with gentle to open fold varies from non-plunging to nearly moderately plunging folds. Most of the faults have parallel orientation to the fold axis, indicated this pattern probably originated at the same period of deformation due to warping and uplifting. Sejumlah data struktur geologi yang terdapat di sepanjang jalur tol Timur-Barat rute 67 daerah Baling telah digunakan untuk menguraikan karakteristik struktur dari Formasi Semanggol yang terdiri atas batu lempung hitam, batu pasir, batu pasir tufaan, tuf, para-konglomerat, batu serpih yang mengandungi silika dan batu rijang. Daerah ini dipotong oleh dua pasang patahan utama yang berarah NW-SE dan NE-SW. Sesar utama di kawasan ini dikenal sebagai Sesar Bok Bak dengan arah NW-SE dan kemiringan sedang hingga curam (40o-88o) sebanding dengan sesar konjugasinya. Dua pasang lipatan berarah NE-SW dan NW-SE juga dapat diidentifikasi di kawasan ini dimana sebagian besar dari lipatan tersebut merupakan lipatan simetri yang landai hingga terbuka dan bervariasi dari sudut penunjamannya dari tidak menunjam sama sekali hingga menunjam sedang. Kebanyakan dari sesar ini berorientasi sejajar dengan sumbu lipatan, mengindikasikan bahwa model ini kemungkinan terbentuk pada periode yang sama dengan proses terjadinya deformasi disebabkan oleh proses pelengkungan dan pengangkatan.